Financial education for MSMEs: What is the best financial education delivery method? - Fauziyah, A.; Sulastri, S.; Nadya R., N. (Linguistics and Culture Review, 2022)
This study aims to determine the types of financial education learning techniques for MSMEs in Tasikmalaya City. Financial education after owning a business is no less important than the financial education given at school or college. Based on external factors, learning techniques can affect financial education. The study used a quantitative descriptive method, and data was collected through an interview process using a closed questionnaire to 30 small business entrepreneurs in Tasikmalaya City. The results showed that the dominant learning technique chosen by the Tasikmalaya City MSME beginner entrepreneurs was through online and offline workshops accompanied by adequate time assistance.